Effect of Quality of Service, Quality Products and Citra Company on Customer Satisfaction - Dwi Sefani; Olivia Syanne Nelwan (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
This study aims to find out the partial and simultaneous effects of service quality, product quality and corporate image on customer satisfaction of PT. Bank Capital Indonesia, Tbk Kelapa Gading Branch. The subject of this research is customers who have bank products at PT. Bank Capital Indonesia, Tbk Kelapa Gading Branch. The sample in this study amounted to 71 respondents. The data collection techniques used are questionnaires, literature studies and observations. Data analysis techniques using multiple regression analysis with SPSS 17. Unttuk coefficient determination (Rsquare) obtained by 0.284 or 28.4% and the rest of 71.6% influenced by other factors beyond the model of this study. Partially 23,8% variable of service quality influence to customer satisfaction, 33% variable of product quality influence to customer satisfaction and 20,5% variable of company image have an effect on customer satisfaction. From the partial test result (t test), the three independent variables ie service quality (X1) have sig value 0.020 smaller than 0.05, product quality (X2) has sig value 0.002 smaller than 0.05 company image (X3) has sig value 0.044 smaller than 0.05, so it can be concluded that the quality of service (X1), product kalitas (X2) and corporate image (X3) partially effect on customer satisfaction (Y) at PT. Bank Capital Indonesia, Tbk Kelapa Gading Branch. For simultaneous or simultaneous testing (F test) the quality of service (X1), product calm (X2) and corporate image (X3) significantly influence customer satisfaction (Y) at PT. Bank Capital Indonesia, Tbk Kelapa Gading Branch because the value of F arithmetic is 10,233 and the value of sig 0.000 is smaller than 0,05.